DOES THE USE OF ADJUVANTS ALTER SURFACE TENSION AND CONTACT ANGLE OF HERBICIDE SPRAY DROPLETS ON LEAVES OF Sida SPP. ? - Santos, R. T. S. [UNESP]; Ferreira, M. C. [UNESP]; Viana, R. G. (Univ Federal Vicosa, 2019)
Droplet spreading on plant surfaces may indicate greater efficiency in herbicide application. The aim of this study was to evaluate surface tension and contact angle of the aminopyralid + fluroxypir herbicide droplets associated with adjuvants on the leaf surface of three species of the genus Sida. The experiment was carried out in a completely randomized design, in a 4x2+1 factorial arrangement, with four replications. Four treatments containing two rates of the herbicide (0.04 + 0.08 kg a.i. ha(-1) and 0.08+0.16 kg a.i. ha(-1)) were evaluated, associated or not with the adjuvants vegetable oil, mineral oil and lecthin; and water was used as a control. Surface tension and contact angle of the syringes were measured with a tensiometer. Surface tension was evaluated at 5, 15 and 25 seconds after droplet formation. Contact angle was measured at 5, 15 and 25 seconds after droplet deposition on the adaxial and abaxial surfaces of Sida rhombifolia, S. glaziovii and S. cordifolia. The results were submitted to analysis of variance by the F-test and the means of the treatments were compared by Tukey's test (p>0.05). There was no interaction between the factors for surface tension. The contact angles of S. cordifolia and S. glaziovii were lower after addition of lecthin on the adaxial face. The addition of the adjuvants to the spray solution provided lower contact angles at the rate of 0.04 + 0.08 kg a.i. ha(-1), except for S. rhombifolia, whose contact angle was lower with the spray solution without adjuvant.
Keywords: aminopiralide plus fluroxipir; spreading; Sida cordifolia; Sida glaziovii; Sida rhombifolia